Independence and Adaptability: Building Resilience and Competitiveness for Small and Medium-sized Enterprises in the Digital Era - Rahmi, R.; Mursyidin, M. (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to investigate the impact of independence and adaptability on business actors in Balikpapan City amidst the industrial revolution 4.0. The study focuses on Small and Medium Enterprises (SMEs) in the culinary sector of Balikpapan City, wit h a sample size of 30 business actors. A quantitative research approach utilizing primary data is employed, and data collection is conducted through the distribution of questionnaires. Statistical analysis using SPSS verifies the significance of the variables of independence (X1) and adaptability (X2) on the industrial revolution 4.0 when tested simultaneously. The findings reveal that both independence and adaptability substantially influence the industrial revolution 4.0. This study contributes to the existing literature by shedding light on the relationship between independence, adaptability, and the impact of the industrial revolution 4.0 on business actors. The findings provide valuable insights for policymakers, MSMEs, and stakeholders in Balikpapan City in navigating and harnessing the opportunities brought by the industrial revolution 4.0.